Fine-tuning and remodeling of pectins play a key role in the maintenance of cell adhesion - Grandjean, Cyril; Voxeur, Aline; Chabout, Salem; Jobert, François; Gutierrez, Laurent; Pelloux, Jérôme; Mouille, Gregory; Bouton, Sophie (Frontiers in Plant Physiology, 2024)
Plant cell adhesion is essential for development and stress response and is mediated by the deposition of pectin-rich middle lamella between cell walls. However, the precise control mechanism of cell adhesion remains unclear. The qua2-1 and esmd1-1 mutants provide a better understanding of this process and suggest a signaling pathway triggering the loss and restoration of adhesion via cell wall modifications. This study aims at a better characterization of the production of endogenous oligogalacturonides(OGs) and cell wall structural modifications in the control of cell adhesion in Arabidopsis. From dark-grown hypocotyls of wild type, qua2-1, esmd1-1, and qua2-1/esmd1-1 mutants, we identified seven distinct endogenous OGs, that varied in their degree of polymerization and extent of substitution and in their abundance. The structure of homogalacturonans were further analyzed by enzymatic fingerprint, indicating a change in esterification patterns. Expression analysis of genes encoding pectin-modifying enzymes, including PME, PMEI, and PAE showed significant variations depending on genotypes. Gene expression levels correlated with changes in the structure of homogalacturonans and cell adhesion phenotypes. This study suggests the involvement of a feedback loop between endogenous OGs, the fine-tuning of homogalacturonans structure, and the gene expression of pectin remodeling enzymes in controlling cell adhesion.